Pengaruh Tourist Facilities dan Destination Image Terhadap Revisit Intention Melalui Electronic Word Of Mouth (E-Wom)(Studi Pada Wisata Air Umbul Ponggok) - Wina Widya Rani; Dinalestari Purbawati; Naili Farida (Universitas Diponegoro, 2024)
Abstract: Indonesian tourism has a big opportunity to develop. This sector is predicted to be able to change the dominance of the oil and gas sector as the main contributor to the country's foreign exchange. This research aims to determine the influence of tourist facilities and destination image on revisit intention through electronic word of mouth at the Umbul Ponggok water tourism. This type of research uses explanatory research with a sample size of 100 respondents. The sampling technique uses non-probability sampling with a purposive sampling method. In analysing the data, the writer used SmartPLS SEM 4 For Windows software. The results of this study show that tourist facilities have a significant influence on electronic word of mouth, destination image has a significant influence on electronic word of mouth, tourist facilities have an insignificant influence on revisit intention and destination image has a significant influence on revisit intention. In this research, it was also found that tourist facilities and destination image have an indirect influence on revisit intention through electronic word of mouth on the Umbul Ponggok water tourism. The suggestion in this research is about the management improve existing public facilities for the convenience of visitors, such as parking lots, toilets and prayer rooms.Keywords: revisit intention; tourist facilities; destination image and electronic word of mouthAbstraksi: Pariwisata Indonesia memiliki peluang yang sangat besar untuk dikembangkan. Sektor ini digadang – gadang dapat menggeser dominasi sektor migas sebagai penyumbang utama devisa negara. Penelitian ini bertujuan untuk mengetahui pengaruh tourist facilities dan destination image terhadap revisit intention melalui electronic word of mouth pada wisata air Umbul Ponggok. Teknik pengambilan sampel menggunakan non probability sampling dengan metode purposive sampling. Pada analisis data menggunakan software SmartPLS SEM 4 For Windows. Hasil penelitian ini menunjukkan bahwa tourist facilities memiliki pengaruh signifikan terhadap electronic word of mouth, destination image memiliki pengaruh yang signifikan terhadap electronic word of mouth, tourist facilities memiliki pengaruh yang tidak signifikan terhadap revisit intention dan destination image memiliki pengaruh yang signifikan terhadap revisit intention. Dalam penelitian ini juga ditemukan bahwa tourist facilities dan destination image memiliki pengaruh tidak langsung terhadap revisit intention melalui electronic word of mouth pada wisata air Umbul Ponggok. Saran dalam penelitian ini adalah pihak pengelola meningkatkan fasilitas publik yang ada demi kenyamanan pengunjung seperti tempat parkir, toilet dan mushola.Kata Kunci: revisit intention; tourist facilities; destination image dan electronic word of mouth